Knowledge, Attitude and Practice of COVID-19 among Nurses at Mayo Hospital Lahore: Knowledge, Attitude and Practice of COVID-19 among Nurses - Batool, Masooma; Afzal, Ambar; Naveed, Sarah; Sattar, Shamim; Rehman, Nargis Abdul (Pakistan Journal of Health Sciences, 2023)
COVID-19 is an unparalleled global challenge, necessitating unprecedented interventions. It emerged as a new and highly contagious virus (SARS-CoV-2), causing high mortality rates and overwhelming healthcare systems. Nevertheless, prior experience with coronaviruses and recent epidemics has provided a foundation for effective infection control and the rapid development of vaccines and treatments. Objective: To assess knowledge attitude and practices regarding COVID-19 among nurses of Mayo Hospital Lahore. Methods: COVID-19 is a unique global dilemma that requires unheard-of remedies. It was a brand new, extremely contagious virus called SARS-CoV-2 that had a devastating impact on health systems and caused high mortality rates. But recent epidemics and past experience with coronaviruses have laid the groundwork for rapid development of vaccines and treatments, as well as effective infection control. Results: The response rate was 100%. The mean age was 3.26+1.474. Among 90 study participants 11(11.2%) were 18-20years, 31(31.6%) were between 21-25years, 3 (3.1%) between 26-30 years, 35 (35.7%) between 31-35years and 11(11.2%) between 36-40years. Further, out of 90 study participant the overall proportion of knowledge attitude and practice were 72.2%, 36.2%, and 63.3% respectively. Conclusions: The overall level of knowledge and practice among nurses was good. However, the attitude was relatively low. National and regional ministry of health should continue efforts and battling of this pandemic disease since it’s still spreading all over the world.